Non-invasive cardiac kinetic energy distribution: a new marker of heart failure with impaired ejection fraction (KINO-HF) - De Keyzer, Eva; Hossein, Amin; Rabineau, Jeremy; Morissens, Marielle; Almorad, Alexandre; van de Borne, Philippe (Frontiers in Cardiovascular Medicine, 2023)
BACKGROUND: Heart failure (HF) remains a major cause of mortality, morbidity, and poor quality of life. 44% of HF patients present impaired left ventricular ejection fraction (LVEF). Kinocardiography (KCG) technology combines ballistocardiography (BCG) and seismocardiography (SCG). It estimates myocardial contraction and blood flow through the cardiac chambers and major vessels through a wearable device. Kino-HF sought to evaluate the potential of KCG to distinguish HF patients with impaired LVEF from a control group. METHODS: Successive patients with HF and impaired LVEF (iLVEF group) were matched and compared to patients with normal LVEF ≥ 50% (control). A 60 second KCG acquisition followed cardiac ultrasound. The kinetic energy from KCG signals was computed in different phases of the cardiac cycle ( (iK systolic; ΔiK diastolic) as markers of cardiac mechanical function. RESULTS: Thirty HF patients (67 [59; 71] years, 87% male) were matched with 30 controls (64.5 [49; 73] years, 87% male). SCG ΔiK diastolic, BCG iK systolic, BCG ΔiK diastolic were lower in HF than controls (p<0.05), while SCG iK systolic was similar. Furthermore, a lower SCG iK systolic was associated with an increased mortality risk during follow-up. CONCLUSIONS: KINO-HF demonstrates that KCG can distinguish HF patients with impaired systolic function from a control group. These favorable results warrant further research on the diagnostic and prognostic capabilities of KCG in HF with impaired LVEF.